Gender Gaps in the Evaluation of Research: Evidence from Submissions to Economics Conferences - Laura Hospido; Carlos Sanz (Institute of Labor Economics (IZA), 2019)
We study gender differences in the evaluation of submissions to economics conferences. Using data from the Annual Congress of the European Economic Association (2015-2017), the Annual Meeting of the Spanish Economic Association (2012-2017), and the Spring Meeting of Young Economists (2017), we find that all-female-authored papers are 3.2 p.p. (6.8%) less likely to be accepted than all-male-authored papers. This gap is present after controlling for (i) number of authors, (ii) referee fixed effects, (iii) field, (iv) cites of the paper at submission year, (v) previous publication record of the authors, and (vi) the quality of the affiliations of the authors. We also find that the gap is entirely driven by male referees - female referees evaluate male and female-authored papers similarly, but male referees are more favorable towards papers written by men.
Keywords: A1; J16; 330; economics profession; academic labor market; gender